Memory and Space: Towards an Understanding of the Cognitive Map - Schiller, Daniela; Eichenbaum, Howard; Buffalo, Elizabeth A; Davachi, Lila; Foster, David J; Leutgeb, Stefan; Ranganath, Charan (The Journal of neuroscience, 2015)
More than 50 years of research have led to the general agreement that the hippocampus contributes to memory, but there has been a major schism among theories of hippocampal function over this time. Some researchers argue that the hippocampus plays a broad role in episodic and declarative memory, whereas others argue for a specific role in the creation of spatial cognitive maps and navigation. Although both views have merit, neither provides a complete account of hippocampal function. Guided by recent reviews that attempt to bridge between these views, here we suggest that reconciliation can be accomplished by exploring hippocampal function from the perspective of Tolman's (1948) original conception of a cognitive map as organizing experience and guiding behavior across all domains of cognition. We emphasize recent studies in animals and humans showing that hippocampal networks support a broad range of domains of cognitive maps, that these networks organize specific experiences within the contextually relevant map, and that network activity patterns reflect behavior guided through cognitive maps. These results are consistent with a framework that bridges theories of hippocampal function by conceptualizing the hippocampus as organizing incoming information within the context of a multidimensional cognitive map of spatial, temporal, and associational context. Research of hippocampal function is dominated by two major views. The spatial view argues that the hippocampus tracks routes through space, whereas the memory view suggests a broad role in declarative memory. Both views rely on considerable evidence, but neither provides a complete account of hippocampal function. Here we review evidence that, in addition to spatial context, the hippocampus encodes a wide variety of information about temporal and situational context, about the systematic organization of events in abstract space, and about routes through maps of cognition and space. We argue that these findings cross the boundaries of the memory and spatial views and offer new insights into hippocampal function as a system supporting a broad range of cognitive maps.